(untitled) (Research, Society and Development, 2020)
The term “gut-brain axis” has been widely used in the study of communication between the gastrointestinal tract and the central nervous system, a vital relationship for the maintenance of homeostasis and whose imbalance can result in changes in the response to stress and in behavior. This review aims to present and discuss the findings of studies about the gut-brain axis and the possible relationship between intestinal dysbiosis and mental disorders. The guiding question was: "How can intestinal health affect the brain and its functioning?" Of fifty articles found, seven were selected to integrate this review, all published in English. The findings of all articles discussed in this review demonstrate a direct and significant impact of the intestinal microbiota on the central nervous system, observing behaviors related to anxiety, depression and stress in the face of changes in the microbiota.